Taxonomic notes on Acanthomegabunus Tsurusaki, Tchemeris & Logunov 2000 (Arachnida: Opiliones: Phalangiidae), with a description of the new species A. altaicus sp. n. from the Altai Mountains of Russia and NE Kazakhstan - Tchemeris, A. N. (Zootaxa, 2015)
The genus Acanthomegabunus Tsurusaki, Tchemeris & Logunov 2000 is diagnosed and redescribed. A key to species is presented. A new species, Acanthomegabunus altaicus sp. n. from the Аltai Mountains of Russia and NE Kazakhstan is diagnosed, described and figured; its distribution is mapped, along with new records of A.sibiricus Tsurusaki, Tchemeris & Logunov 2000.